2023
DOI: 10.1097/hcr.0000000000000796
|View full text |Cite
|
Sign up to set email alerts
|

Home-Based Cardiac Rehabilitation Among Patients Unwilling to Participate in Hospital-Based Programs

Abstract: Home-Based CR of Patients That Declined Traditional CR 33C ardiac rehabilitation (CR) is well recognized as an essential intervention for the secondary prevention of coronary artery disease, heart failure (HF), and future heart-related complications. 1 Benefits of CR include improvements in morbidity, physical activity (PA) level, exercise capacity, and quality of life as well as decreased rate of hospital admissions. 2 A viable alternative to traditional, center-based cardiac rehabilitation (CBCR) is asynchro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…A crucial objective of our study was to identify a more effective approach conducive to improved adherence to cardiac rehabilitation goals. Our prior research [ 51 , 52 ], alongside other studies [ 53 ], has indicated that remote rehabilitation programs successfully achieve compliance with aerobic objectives but consistently fall short in terms of adherence to prescribed strength training.…”
Section: Discussionmentioning
confidence: 99%
“…A crucial objective of our study was to identify a more effective approach conducive to improved adherence to cardiac rehabilitation goals. Our prior research [ 51 , 52 ], alongside other studies [ 53 ], has indicated that remote rehabilitation programs successfully achieve compliance with aerobic objectives but consistently fall short in terms of adherence to prescribed strength training.…”
Section: Discussionmentioning
confidence: 99%
“…The cardiopulmonary test does not evaluate diaphragm function The international guidelines for RC give strong indications on the fact that, before undertaking a rehabilitation cycle, the patient must undergo a cardiopulmonary exercise test (CPET), measuring peak oxygen consumption (VO2peak), both for people who will follow a procedure in specialized centers and for physical activity carried out at home [17,47]. The test allows you to obtain data under stress; the objective is to identify a suitable CR path for each patient [9].…”
Section: Diaphragm Overloadmentioning
confidence: 99%